2002
DOI: 10.1097/00005768-200201000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Vertical jump coordination: fatigue effects

Abstract: It was suggested that the neural input used in the fatigued condition did not constitute an optimal solution and may have played a role in decreasing maximal jump height achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
6
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 30 publications
7
143
6
15
Order By: Relevance
“…Fatigue may be produced metabolically, or muscularly, which leads to a decline in performance. A change in coordination (neural input), a change in the muscles' functional ability to produce force, or a combination of the two may be the cause of the decline in performance (Rodacki, Fowler, & Bennett, 2002). It has been shown that heavy resistance loading led to decreases in maximal neural activation and decreased explosive force production of the exercised muscles (Hakkinen, 1993), thus affecting performance.…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue may be produced metabolically, or muscularly, which leads to a decline in performance. A change in coordination (neural input), a change in the muscles' functional ability to produce force, or a combination of the two may be the cause of the decline in performance (Rodacki, Fowler, & Bennett, 2002). It has been shown that heavy resistance loading led to decreases in maximal neural activation and decreased explosive force production of the exercised muscles (Hakkinen, 1993), thus affecting performance.…”
Section: Fatiguementioning
confidence: 99%
“…Further, muscle fatigue leads to contractile force loss and muscle activation timing disturbance, which may then affect joint instability as was well as biomechanical alterations of the task (Vila-Cha, Carvalho, Machado, Conceicao, & Vilas Boas, 2005). As such, researchers have sought to determine the effects of fatigue on various jump-related tasks, such as landing from a jump (Pappas et al, 2007;Smith, Sizer, & James, 2009), performing a drop jump (Moran et al, 2009), performing a maximal vertical jump (Rodacki et al, 2002), and single-leg hop testing (Augustsson et al, 2006). Results have provided useful information on training programs to offset the effects of fatigue and improve landing technique, drop jump training, jump height performance, and functional performance when fatigued, all of which are especially important at the end of sporting events when fatigue is greater and injuries are more likely to occur (Dugan & Frontera, 2000).…”
Section: Fatiguementioning
confidence: 99%
“…El KT puede estimular mecanorreceptores cutáneos y mejorar la información de la señal del movimiento o la posición de las articulaciones, lo cual podría mejorar la coordinación (16). Así mismo se conoce que la ejecución del salto depende de la coordinación de las acciones segmentarias del cuerpo humano, que están determinadas por la interacción entre las fuerzas musculares y los momentos netos que tienen que generarse alrededor de las articulaciones para cumplir las exigencias mecánicas de la tarea (17).…”
Section: Discussionunclassified
“…A hipótese inicial desse estudo era que o comportamento do processo de fadiga e as alterações EMG durante um protocolo intermitente de saltos verticais difeririam das respostas encontradas em protocolos contínuos (BOSCO et al,1986;STROJNIK;KOMI, 2000;RODACKI;FOWLER;BENNETT, 2002;HESPANHOL et al, 2007;MCCAULLEY et al, 2007) predominantes no estudo deste gesto desportivo. Entretanto, como a característica do protocolo é bem próxima ao realizado em uma partida de voleibol, era esperado que as atletas não atingissem um estado de exaustão, mesmo diante da grande quantidade de saltos totais executados.…”
Section: Discussionunclassified
“…A divergência entre respostas neuromusculares pode estar relacionada com o menor efeito nos componentes contráteis e elásticos que potencializam o desempenho quando o protocolo é intermitente, como já citado na literatura (HORITA et al, 2002). Nessa perspectiva, a maioria dos estudos consideram somente as perspectivas neuromusculares e bioenergéticas ao avaliar a causa e o processo de instalação de fadiga na ação do salto vertical, induzidos pelos efeitos de protocolos contínuos e exaustivos (Bosco et al, 1986;Horita et al, 1996;Strojnik;Komi, 2000;Rodacki;Fowler;Bennett, 2002;McCaulley et al, 2007), diferentes da situação real de jogo.…”
Section: Discussionunclassified